Pelaksanaan Supervisi Akademik Kepala Madrasah dalam Meningkatkan Kinerja dan Mutu Guru - Azhar, Azhar; Syarfuni, Syarfuni; Rahmattullah, Rahmattullah (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The implementation of education is an effort to improve human resources. Madrasah is also one of the means, because madrasah is a formal educational institution which in the implementation of education requires madrasah personnel to evaluate, supervise and improve the teaching and learning process carried out by teachers requires supervision. This study aims to determine the implementation of academic supervision in improving teacher performance and quality. This research is qualitative research with a type of field research. The techniques used in collecting data in this study are observation, interviews, and documentation. While the technique in analyzing data is with three stages, namely data reduction, data presentation, and conclusion drawing. The results of data analysis showed that the implementation of academic supervision of the head of the madrasah by visiting directly to class, and sometimes only listening to the course of learning outside the classroom. The results of academic supervision carried out by the head of MTs Negeri 4 Pidie have been running in accordance with existing regulations, including class visits, class observations, inter visitation, personal conversations, and teacher meetings